On discrete event simulation of time-variance defense mechanism against low-rate denial of service - Hussin, Masnida; Raja Mahmood, Raja Azlina; Muhammed, Abdullah (Science and Knowledge Research Society, 2015)
Due to the widely deployed wide-area computer and communications networks; the Internet has undergone rapid development and has become indispensable in our daily lives. However, the Internet has caused many security problems and financial loss due to the unauthorized access. As network capability grows faster and larger, network security has become a rather important issue from both theoretical point of view and engineering applications. In this study we proposed time-variance defense mechanism against low-rate denial of service (LoRDoS) attacks. The defense mechanism considered in this study is based on modifying a way in which server behaves by using service time. We adjusted Random Waiting Time (RWT) to create deceptive server behavior while effectively scheduling incoming tasks in the queue. RWT reduces LoRDoS attack by shifting a response time to a position that not controlled by the attacker. The proposed defense technique has been implemented through Discrete Event Simulation (DES). Our approach enables in reducing processing delay while optimizing the computing resources.